2013
DOI: 10.1121/1.4821988
|View full text |Cite
|
Sign up to set email alerts
|

Beamforming of sound from two-dimensional arrays using spatial matched filters

Abstract: Fully-sampled two-dimensional (2D) arrays can have two-way focusing of the ultrasound beam in both lateral directions leading to high quality, real-time three-dimensional (3D) imaging. However, fully-sampled 2D arrays with very large element counts (>16 000) are difficult to manufacture due to interconnect density and large element electrical impedance. As an alternative, row-column or crossed electrode arrays have been proposed to simplify transducer fabrication and system integration. These types of arrays c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A modified delay-and-sum (DAS) beamformer using the methods described in [11] is employed, where the size of the line elements are taken into account. The second beamformer uses the spatial matched filter (SMF) [24]- [26] methods for processing the RF data. Here the received signals are modeled in Field II and the signal shape is used as a spatial matched filter in the beamformation [24].…”
Section: Introductionmentioning
confidence: 99%
“…A modified delay-and-sum (DAS) beamformer using the methods described in [11] is employed, where the size of the line elements are taken into account. The second beamformer uses the spatial matched filter (SMF) [24]- [26] methods for processing the RF data. Here the received signals are modeled in Field II and the signal shape is used as a spatial matched filter in the beamformation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial matched filter (SMF) beamforming is an algorithm, in which the impulse responses in transmission and in reception are considered for every point, unlike the DAS which assumes the impulse responses to be like delta functions [4], [8], [9]. Due to acoustically equivalent line-elements via row-column addressing the 2-D matrix array, SMF has the potential to improve the spatial resolution and the SNR.…”
Section: Introductionmentioning
confidence: 99%
“…Due to acoustically equivalent line-elements via row-column addressing the 2-D matrix array, SMF has the potential to improve the spatial resolution and the SNR. In [4], based on simulations, it was shown that SMF beamforming provides comparable results like synthetic aperture imaging with DAS beamforming. However this paper investigates SMF beamforming using synthetic aperture imaging.…”
Section: Introductionmentioning
confidence: 99%
“…different techniques to improve the resolution, sensitivity, or frame rate of row-column-addressed arrays were explored theoretically by daher et al [11], [12] and yen [13] using synthetic aperture techniques and spatial matched filters. recently, rasmussen and Jensen used a fully addressed 32 × 32 array in a measurement study to compare the imaging performance of a fully addressed array to that of a row-column-addressed array [14].…”
mentioning
confidence: 99%